Somatic genome alterations in relation to age in lung adenocarcinoma. Issue 8 (28th March 2019) - Meucci, Stefano; Keilholz, Ulrich; Heim, Daniel; Klauschen, Frederick; Cacciatore, Stefano
Abstract : Lung adenocarcinoma (LUAD) is the most common cause of global cancer‐related mortality and the major risk factor is smoking consumption. By analyzing 486 LUAD samples from The Cancer Genome Atlas, we detected a higher mutational burden among younger patients in the global cohort as well as in the TP53‐ mutated subcohort. The interaction effect of patient age and TP53 mutations significantly affected the mutational rate of younger TP53 ‐mutated patients. Furthermore, we detected a significant enrichment of the smoking‐related signature SI4 (SI4) among younger TP53 ‐mutated patients, meanwhile the age‐related Signature 1 (SI1) significantly increased in proportion to patient age. Although present and past smoking is reported in the TP53 wild‐type patients, we observed a lower average number of somatic mutations, with no correlation with patient age. Overall, TP53 mutations were significantly higher in younger patients and mainly characterized by SI4 and Signature 24 (SI24). Therefore, TP53 seemed to acquire a particular sensitivity to smoking related C>A mutations in younger patients. We hypothesize that TP53 mutations at a younger age might be a crucial factor enhancing the sensitivity to smoking‐related mutations leading to a burst of somatic alterations. The mutational profile of cancer cell might reflect the mutational processes operative in aging in a given tissue. Therefore, TP53 ‐mutated and TP53 wild‐type patient groups might represent phenotypes which endure aging‐related mutational processes with different strength. Our study provides indications of age‐dependent differences in mutational backgrounds that might be relevant for cancer prevention and age‐adjusted treatment approaches. Abstract : What's new? In lung adenocarcinoma, previous analyses have reported a higher mutational rate among younger patients. These authors investigated the genetic mechanisms at work, drawing on data from The Cancer Genome Atlas (TCGA). They found that in patients whose tumors carried TP53 mutations, younger age correlated with higher mutational load. This association was not seen with wild‐type TP53. Younger patients were also more likely to have the smoking‐related signature 4 mutation profile. The authors suggest that TP53 mutations in younger patients may increase sensitivity to smoking‐related somatic mutations.